The Yanomami sociopolitical dynamics in the context of the Hutukara creation: the Pata Thëpë and the emergency of young political leaderships - Carvalho, Maria Auxiliadora Lima de (Textos e Debates, 2016)
The current study is an effort to understand the Yanomami sociopolitical dynamic in the context of mobilization and articulation that preceded the establishment of Hutukara Yanomami Association; in that context, new patterns of dialogs and knowledge were established, fact that has delineated new forms of relationship between youth and elder leaders. From reads in ethnology, history and I my own ethnography work, I try to understand the place of the new organization in the sociopolitical dynamic of Yanomami and its implication for the local groups and also in the relationship between traditional and youth leaders. I try to show that speech and knowledge are the two major principles that connect the youth and traditional leaders; the choice of youth leaders as major political speaker does not mean the elder’s loss of power; the Yanomami see the presence of the youth in the meetings as necessary, due to the necessity of decoding their relationship with non-Indians.